Efeito de reguladores de crescimento vegetal no crescimento e componentes de rendimento da cultivar de soja NEO 610 IPRO - Steffler, Vinícius Augusto (2023)
Different types of management are being researched on crops. Some different practice is needed to make it easier to harvest the crop in the field without having to suffer any damage, and the use of growth regulators is one of these. This study aimed to test the efficiency of different growth regulators in soybean cultivation. The experiment was set up in the municipality of Não-Me-Toque and consisted of different products used as growth regulators and mechanical mowing in the soybean crop, with 9 treatments and 4 replications. The soybean cultivar used was NEO 610 IPRO from the Neogen® company of the DonMario® seeds group. The products were applied at the V5 and V6 stages of the plants and mowed at the V6 and V8 stages. Plant height, the height of first node insertion, number of nodes on the main stem, number of lateral branches, number of nodes on the branches, number of pods (main stem, lateral branch, and total), number of grains per plant from all the pods on the plants, grain weight, leaf area index, and grain yield were evaluated. The variables were analyzed using the SISVAR® statistical program, with the Tukey test of means at a 5% probability of error level. Under the conditions in which the work was carried out, it can be concluded that: the variables grain yield, thousand-grain weight, plant height, first node insertion height, number of pods on the main stem, and leaf area index (LAI) showed statistical differences between the treatments. It is worth noting that the treatment with Imazethapyr had higher values in the branches. The treatment that received an application of 2.4 D having the smallest plants, and as a consequence ended up losing productivity due to damage to the plants as a result of stem dystrophy observed in the evaluations. For factors related to yield components such as thousand-grain weight, the treatment with Cinetin+GA3+AIB (Stimulate®) obtained the highest value. More studies are needed in different agricultural years to understand better the action of the products and mechanical mowing management about climatic factors.